The effects of helminth infections on the human gut microbiome: a systematic review and meta-analysis - Walusimbi, Bridgious; Lawson, Melissa A. E.; Nassuuna, Jacent; Kateete, David P.; Webb, Emily L.; Grencis, Richard K.; Elliott, Alison M. (Frontiers in Microbiomes, 2023)
The gut microbiome is important in shaping human health. One key factor that has been proposed to affect the gut microbiome is helminth infection. Unravelling the association and/or interaction between helminth infections and the gut microbiome may reveal new insights into the mechanisms through which parasitic worms impact the prognosis of infections and diseases. While considerable work has gone into reviewing data on the effect of helminth infection on gut microbiome in animal studies, less attention has been given to this area of research in human studies. This study set out to address this through an exhaustive systematic review of literature. Articles were identified through EMBASE, MEDLINE, Web of Science and Science Direct following a registered protocol (PROSPERO). After assessing methodological quality (ICROMS) and publication bias, a random effects meta-analysis was performed to investigate the overall effect that intestinal parasites can have on the human gut microbiome using alpha- and beta-diversity metrics and adjusting for age, sex and antihelminthic treatment taken by individuals. A total of 19 out of 3466 articles were included in the final meta-analysis. Our results show that helminth infection increases the host bacterial diversity, as well as microbial richness. This work further contributes to the understanding of how the gut microbiome structure changes depends on whether one is infected with helminths or not. It also lays the foundation for future research aimed at establishing how these interactions could explain the disparity in phenotypes such as infection, disease and vaccine responses reported in different regions worldwide. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42020192182.